Replication and the Establishment of Scientific Truth - Iso-Ahola, Seppo E. (Frontiers in Psychology, 2020)
The idea of replication is based on the premise that there are empirical regularities or universal laws to be replicated and verified, and the scientific method is adequate for doing it. Scientific truth, however, is not absolute but relative to time, context, and the method used. Time and context are inextricably intertwined in that time (e.g., Christmas Day vs. New Year’s Day) creates different contexts for behaviors and contexts create different experiences of time, rendering psychological phenomena inherently variable. This means that internal and external conditions fluctuate and are different in a replication study vs. the original. Thus, a replication experiment is just another empirical investigation in an ongoing effort to establish scientific truth. Neither the original nor a replication is the final arbiter of whether or not something exists. Discovered patterns need not be permanent laws of human behavior proven by the pinpoint statistical verification through replication. To move forward, phenomenon replications are needed to investigate phenomena in different ways, forms, contexts, and times. Such investigations look at phenomena not just in terms the magnitude of their effects but also by their frequency, duration, and intensity in labs and real life. They will also shed light on the extent to which lab manipulations may make many phenomena subjectively conscious events and effects (e.g., causal attributions) when they are nonconsciously experienced in real life, or vice versa. As scientific knowledge in physics is temporary and incomplete, should it be any surprise that science can only provide “temporary winners” for psychological knowledge of human behavior?